Zn-based eutectic mixture as anolyte for hybrid redox flow batteries - Wang, Yiyu; Niu, Zhihui; Zheng, Qi; Zhang, Changkun; Ye, Jing; Dai, Gaole; Zhao, Yu; Zhang, Xiaohong (Scientific reports, 2018)
Developing greener batteries with new chemistries is a formidable challenge, and a major focus for years to come. Redox flow batteries are receiving increasing research interest for grid-scale electrochemical energy storage owing to their unique architecture. However, challenges still remain by their low energy density as well as corrosive and/or toxic electrolytes. An anolyte based on aprotic Zn deep-eutectic-solvent, which uses low cost, abundant and environmentally benign materials, exhibits a utilizable concentration of Zn 2+ ca. 1.7 M, resulting in a reversible volumetric capacity of ca. 90 A h·L −1 . Combined with high efficiencies and relatively low redox potential of −1.12 V vs. Ag/AgCl, such an anolyte provides an alternative way to explore a family of anolytes using new chemistries for rechargeable Zn batteries that meet the criteria for grid-scale electrical energy storage.